2019
DOI: 10.28991/esj-2019-01185
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Corrosion Behaviors of Bare Ti and TiO2

Abstract: In this study, titanium (Ti) surface was anodized by applying 60 voltages for two hours to form titanium dioxide (TiO2) with anodization method. After anodization procedure, comparison of corrosion behaviors of the bare titanium and TiO2 coated titanium was examined in 1 M KOH solution by using electrochemical methods such as anodic and cathodic current-potential curves and electrochemical impedance spectroscopy (EIS). Cyclic voltammetry (CV) and energy dispersive X-ray (EDX) were used to characterize bare Ti … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Adsorption is a promising technique because of its ease of use, increased proficiency, low-cost requirements, and great reproducibility [7]. Furthermore, because the process is usually reversible, the adsorbents can be readily regenerated and reused [8]. Additionally, the availability of a diverse spectrum of adsorbents makes the adsorption process adaptable to specific requirements [9].…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption is a promising technique because of its ease of use, increased proficiency, low-cost requirements, and great reproducibility [7]. Furthermore, because the process is usually reversible, the adsorbents can be readily regenerated and reused [8]. Additionally, the availability of a diverse spectrum of adsorbents makes the adsorption process adaptable to specific requirements [9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the irreversibility phenomenon of various types of nanofluid flow was investigated by many researchers [26][27][28][29][30][31][32]. Some researchers reported data by demonstration of experimental work [33][34][35][36][37][38]. To the best of author's knowledge, upto now, no theoretical results are given for the effects of heat transfer and irreversibility of hydromagnetic Fe3O4-ethylene glycol nanofluid flow in a shrinking wall with porous medium, heat sink or source and thermal radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results obtained are compared with the analytical ones for both the beam-column joints reinforced with steel and GFRP reinforcements. Döner [24] studied the corrosion behavior of bare titanium and titanium dioxide. The main result showed that higher polarization resistance was obtained on porous TiO2 than that of bare titanium.…”
Section: Introductionmentioning
confidence: 99%